How Costly Are Business Cycle Volatility and Inflation? A Vox Populi Approach - Dimitris Georgarakos; Kwang Hwan Kim; Olivier Coibion; Myungkyu Shim; Myunghwan Andrew Lee; Yuriy Gorodnichenko; Geoff Kenny; Seowoo Han; Michael Weber (Institute of Labor Economics (IZA), 2025)
Using surveys of households across thirteen countries, we study how much individuals would be willing to pay to eliminate business cycles. These direct estimates are much higher than traditional measures following Lucas (2003): on average, households would be prepared to sacrifice around 5-6% of their lifetime consumption to eliminate business cycle fluctuations. A similar result holds for inflation: to bring inflation to their desired rate, individuals would be willing to sacrifice around 5% of their consumption. Willingness to pay to eliminate business cycles and inflation is generally higher for those whose consumption is more pro-cyclical, those who are more uncertain about the economic outlook, and those who live in countries with greater historical volatility.
Keywords: E3; E4; E5; 330; cost of business cycles; willingness to pay; inflation